2013
DOI: 10.1089/ars.2012.5027
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidβ-Peptide (1–42)-Induced Oxidative Stress in Alzheimer Disease: Importance in Disease Pathogenesis and Progression

Abstract: Significance: Alzheimer disease (AD) is an age-related neurodegenerative disease. AD is characterized by progressive cognitive impairment. One of the main histopathological hallmarks of AD brain is the presence of senile plaques (SPs) and another is elevated oxidative stress. The main component of SPs is amyloid beta-peptide (Ab) that is derived from the proteolytic cleavage of amyloid precursor protein. Recent Advances: Recent studies are consistent with the notion that methionine present at 35 position of Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
345
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(358 citation statements)
references
References 175 publications
(132 reference statements)
11
345
0
2
Order By: Relevance
“…High levels of HNE have been detected in amyloid b plaques and in the cerebrospinal fluid in Alzheimer's patients. 27 The accumulation of HNE-modified amyloid b-peptides has been shown to inhibit the proteasome, 28 and the resulting accumulation of ubiquitinated modified proteins leads to a proinflammatory response (cyclo-oxygenase 2, prostaglandins). This contributes to neurodegeneration.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%
“…High levels of HNE have been detected in amyloid b plaques and in the cerebrospinal fluid in Alzheimer's patients. 27 The accumulation of HNE-modified amyloid b-peptides has been shown to inhibit the proteasome, 28 and the resulting accumulation of ubiquitinated modified proteins leads to a proinflammatory response (cyclo-oxygenase 2, prostaglandins). This contributes to neurodegeneration.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%
“…Aβ plays a central role in the pathogenesis of AD, by causing neurodegeneration and disrupting the cognitive function although the molecular pathways leading to neuronal impairment are not yet fully elucidated. It has been shown that early formed pre-fibrillar aggregates of Aβ are mainly endowed with cytotoxicity, whereas mature fibrils are much less toxic or even harmless [86][87][88].…”
Section: Involvement Of Sam In Oxidative Stress and Neurodegenerationmentioning
confidence: 99%
“…Aβ 1-42 -induced oxidative stress was considered as crucial to the pathophysiology of AD [6]. In this study, oxidative stress was assessed by measuring the intracellular ROS level using the ROS-sensitive fluorescence probe DCF.…”
Section: Cntf Protects Sh-sy5y Cells From Aβ 1-42 -Induced Oxidative mentioning
confidence: 99%